Buckling resistance of partially encased columns under fire - Piloto, P.A.G. (2017)
The fire resistance of partially encased columns depends on the temperature evolution during fire exposure. This work aims to evaluate the effect of the balanced summation model on the design of the buckling load of Partially Encased Columns under fire situation. New improvements will be presented to assess fire resistance, suggesting some modification in the Annex G of Eurocode EN 1994-1-2. The advanced calculation method is based on the 3D modelling of the Partially Encased Column, using steel profiles ranging from IPE200 to IPE500 and HEB160 to HEB500, and using different buckling lengths. An incremental and interactive procedure is used to solve the geometric and material non-linear behaviour. The temperature effect is taken into account, using the uncouple thermal-structural analysis. The results obtained by the numerical simulations are in good agreement with the new simple calculation method and are also useful to prescribe the buckling curve that best fits the 3D simulation results.